Operations of semiconductor lasers under optical feedback with linewidth enhancement factor - Abdulrhmann, Salah (AIP conference proceedings, 2018)
We investigate numerically influence of linewidth enhancement factor and injection current on the route to chaos and associated operation states of semiconductor lasers subject to optical feedback. Numerical solutions of a time-delay rate equations are employed to construct bifurcation diagrams. The simulation result shows that changes in the linewidth enhancement factor cause important changes in the route to chaos and the laser states. The state of the laser is identified into six distinct regimes, namely, continuous wave, periodic oscillation, period doubling or two, period-three, period-four oscillations and chaos, which is depending on the linewidth enhancement factor, optical feedback strength and injection current level. Decreasing the injection current and increasing the linewidth enhancement factor stimulate the laser to be more stable and operate in continuous and periodic oscillations.